Checklist of Helminth Parasites of Cyprinids from Poonch River and its Tributaries, Jammu and Kashmir, India - Ahmed, Mumtaz; Chaudhary, Anshu; Ahmed, Farooq; Kumar, Yougesh; Singh, Hirdaya S. (The Scientific Temper, 2021)
Parasitological studies on helminths of freshwater fish in district Poonch, Jammu and Kashmir, India is scarce that should be well-understood in order to assess their biodiversity. As compare to other regions in Jammu and Kashmir, India, less comprehensive studies is available with unpublished records. Here, we present a list of parasites that we have collected comprises a list of helminth parasites, their host species, and locality. This study contributes to the diversity of helminth parasites from River Poonch, Jammu and Kashmir, India that helps to identify the lacunae in our knowledge of this region.